Biochemical study for Amoebic dysentery in patients with Entamoeba histolytica in Thi-Qar province/southern Iraq - Fawaz h Sabeeh; Amal Khalaf (Basrah Journal of Veterinary Research)
Entamoeba histolytica is a parasitic protozoan that caused amoebiasis or amoebic dysentery, it is an intestinal disease which infects colon and liver Amoebic dysentery is spread all over the world. E. histolytica is causing the death of human cells and leading to develop invasion, and ulceration of the intestine. However, amebic liver abscess (ALA) considers as major common extraintestinal disease caused by E. histolytica. The current study was designed to estimate the effect of E. histolytica trophozoite on liver functions through the evaluation of some bio-chemical parameters for patients with amebiasis. Blood sample were collected from patients with amoebic dysentery after diagnosed about 100 from stool sample from them microscopically and detected by PCR technique to confirm the infection with am-amebiasis, all sample with amoebiasis were subjected to biochemical study after the separation of serum. Biochemical parameters that included during this study were AST, ALT and ALP. Lipid profile included Triglyceride and Cholesterol as well as some minerals like   Iron, Zinc, and Potassium. The results for the level of AST and ALT were showed a high significant difference (P<0.01) where AST was (22.84+/-7.83) in patients’ compared with (55.36+/-16.8) in control groups and ALT level   Was (20.4+/- 9.37) in patients compared with (47+/-20.1) in control groups. Additionally, there is no significant difference (p>0.05) in ALP level where it was (351.7+/-235.2) in patients with amoebic dysentery compared with (336. 13+/-204.08) in controls group. Triglyceride were also checked in patients with amoebic dysentery and the results showed that a significant difference (p<0.05) between (166.72+/-62.4) in patients and (135. 43+/-45.2) in control groups. Cholesterol level was also checked in patients and the results showed there is no significant difference (P>0.05) between (185.8+/-77.2) in patients and (160.19+/-51.3) in controls groups. In addition, some minerals  were studied during the following study like  Iron,  Zinc, and Potassium for patients with and the results were not showed a significant difference (P>0.05) in zinc, potassium and iron where  the level of iron were ( 85.24+/-16.58) in patients compared with ( 81.22+/-15.5) in control groups, while the level of zinc were (108.09+/-24.4) in patients and ( 101.76+/-24.4) in control groups , the level of potassium were (3.73+/-1.89) in patients and compared with ( 3.84+/-1.14) in control groups.